Cultural Change, family transitions and reflexivity in a morphogenetic society (Memorandum: Memória e História em Psicologia, 2011)
The concept of family transition – both normative and non-normative, whether due to internal or to external factors – presupposes the passage from one relatively stable situation to another relatively stable condition. What happens when the relative stability of the transitional stages withers away? What kind of interventions (social policies, personal social services, etc.) can be envisaged in a society that configures the family’s transitions as an unbound morphogenesis of its relations? The family becomes an unceasing transition due to many factors, basically because societal morphogenesis makes the reflexive abilities of families increasingly problematic. The paper suggests that we move beyond the conditional and “muddling through” models of the past. We need to adopt a new model of analysis and intervention, called the ODG-system, which is relational and reflexive. It consists of developing the relational reflexivity of the family as a social system.